Scientific Rigor, Ethics of Publications, and the Temptation of Predatory Journals - R. Mauricio Barría P (Universidad de Antioquia, 2018)
Generation of knowledge is fundamental for progress in different scientific disciplines and professions. Specifically, in health sciences no adequate technical-professional and disciplinary progress can be made if it is not as of research, which, in many cases, has been destined and confined to the academic setting. It is precisely in this scenario that the idea of publishing has prevailed, has been promoted, and required, which has pressured the scientific and academic community in the search for this objective, sometimes in a not very rigorous manner. (1) According to the value assigned to scientific production if not published, they are limited and restricted in their hiring possibilities and academic promotions with the added impossibility of opting for improved wages.